Articulating Africa-Wide Policy Issues for Adaptation and Mitigation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Presentation by Lindiwe Sabanda (FANRPAN). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya